1978
DOI: 10.1677/joe.0.0790255
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Control by the Testis of Gonadotrophin Secretion: An Examination of the Inhibin Hypothesis

Abstract: Spermatogenesis in rats was interrupted by local X-irradiation, heat or ligation of the testicular efferent ducts. A significant and specific rise in the serum level of FSH occurred 5--8 days after ligation of the efferent ducts, reaching twice the value observed in sham-operated controls by 21 days after the operation. After the testes were heated to 43 degrees C for 30 min, the serum levels of both LH and FSH were raised within 3 days and remained so up to 50 days after treatment. After X-irradiation, no cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
1
4

Year Published

1978
1978
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
9
26
1
4
Order By: Relevance
“…The concentrations of testosterone in the blood were measured by the radioimmunoassy method of Main, Davies & Setchell (1978). The specificity of the testosterone assay relative to testosterone (100%) was only significant with respect to two other androgens: dihydrotestosterone (52-0%) and 5a-androstan-3a,17ß-diol (34-4%).…”
Section: Animal and Methodsmentioning
confidence: 99%
“…The concentrations of testosterone in the blood were measured by the radioimmunoassy method of Main, Davies & Setchell (1978). The specificity of the testosterone assay relative to testosterone (100%) was only significant with respect to two other androgens: dihydrotestosterone (52-0%) and 5a-androstan-3a,17ß-diol (34-4%).…”
Section: Animal and Methodsmentioning
confidence: 99%
“…However, the same authors have observed that the decrease in testicular blood flow induced by irradiation can lead to a slight decrease in the total amount of testosterone entering the general circulation. In the present study in which y rays were used in the same way as X-rays in previous studies (Hopkinson et al, 1978;Main et al, 1978;Delic et al, 1986) (Delic et al, 1986), but has more often been considered to result from the changes induced in the cell-to-cell interactions between the seminiferous tubules and the interstitial compartment (Risbridger et al, 1981 b).…”
Section: Abp Assaymentioning
confidence: 97%
“…Spermatogonia are known to be the most radiosensitive cells in the testis, but if the radiation dose is higher, more differentiated cells can also be destroyed (Shaver, 1953;Oakberg and Di Minno, 1960 Huckins, 1978;Hopkinson et al, 1978;Main et al, 1978;Wang et al, 1983;Pinon-Lataillade et al, 1985;Delic et al, 1986;Kamtchouing et al, 1988;Pineau et al, 1989 (Parvinen, 1982; Sharpe, 1986;J6gou et al, 1988;Verhoeven and Cailleau, 1989 (J6gou et al, 1988). One possible approach to the investigation of this complex aspect of the paracrine regulation of spermatogenesis has been to use different protocols of irradiation which, in vivo, were found to induce different degrees of seminiferous epithelium modification (Rich and De Kretser, 1977;Hopkinson et al, 1978;Vihko et al, 1984;PinonLataillade et al, 1985PinonLataillade et al, , 1988Pineau et al, 1989;Kangasniemi et al, 1990a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier investigations into the hormonal changes that accompany injury to the testes have demonstrated considerable variation in the concentrations of LH and testosterone (Collins et al, 1978 ;Main et al, 1978). Because of this variation, quite large changes in mean values obtained for these hormones are sometimes dismissed as being insignificant.…”
Section: Introductionmentioning
confidence: 99%